Effects of nitrogen level in nutrition solution on growth, yield and quality of strawberries planting in net house at Da Lat - Cao, Thị Làn (Vietnam Academy of Agricultural Sciences, 2023)
The experiment studied the effect of N level in nutrient solution on growth, yield and quality of strawberry fruit was conducted in plastic house in Da Lat. Strawberry seedlings are grown on potted pots containing mixtures of rice husk and cocopeat in proportion 1 : 3. The experiment was designed in completely randomized block with 7 treatments, 3 repetitions. Experimental results showed that the concentration of N in the nutrient solution was strongly correlated with leaf growth and strawberry yield. The leaf stalk growth and yield were highest in nutrient solution with N concentration of 154 - 182 mg/L. Fruit quality was greatly affected by the concentration of N in the nutrient solution. The N concentration of 98 - 182 mg/L could give the best fruit quality. The N concentration of 98 mg/L produced the highest fruit quality and was equivalent to the concentration of N = 182 mg/L. The rate of infected fruits of gray mold rot caused by Botrytis cinerea and anthracnose due to Colletotrichum acutatum in fruit was inversely proportional to the N concentration in nutrient solution. The N concentration of 98 mg/L had the lowest rate of two infected fungi on fruits.